Functional dimorphic enantiostyly in monomorphic enantiostylous species of the subtribe Cassiinae (Fabaceae‐Caesalpinioideae). (19th April 2018) - Almeida, N. M.; Souza, J. T.; Oliveira, C. R. S.; Bezerra, T. T.; Novo, R. R.; Siqueira Filho, J. A.; Oliveira, P. E.; Castro, C. C.
Abstract: Monomorphic enantiostylous species produce flowers with a displacement of the style to the left (L) or right (R) on the same individual, and may exhibit different dynamics for the production of these floral types, which may influence levels of selfing. We investigated the production dynamics of L and R floral types in seven species and a variety of monomorphic enantiostylous species of the genera Senna and Chamaecrista . Our hypothesis was that most species present similar proportions of floral morphs each day. Individuals were classified daily over a period of 7 days according to the functional status, i.e . the proportion of floral morphs as functionally L, R or reciprocal (REC, i.e . similar proportions of the two floral morphs), and also according to the number of consecutive days in which they exhibited the same functional status. All species presented low daily flower production. Most species had individuals classified as functionally R, L and REC, and tend to repeat the same functional status over a few days, although they may change functional status during the flowering period. All species exhibited individuals that were classified as functionally reciprocal when both the daily and total number of flowers produced over 7 days was considered. The occurrence of different functional status has not yet been reported in the literature for enantiostylous species. The distinct strategies observed in the dynamics of floral morph production seemed likely to minimise geitonogamy and to favour cross‐pollination between individuals (xenogamy).